2007
DOI: 10.1001/archpedi.161.11.1026
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Fluoxetine and Cognitive Behavioral Therapy in Adolescents With Major Depression, Behavior Problems, and Substance Use Disorders

Abstract: Fluoxetine and CBT had greater efficacy than did placebo and CBT on one but not both depression measures and was not associated with greater decline in self-reported substance use or CD symptoms. The CBT may have contributed to higher-than-expected treatment response and mixed efficacy findings, despite its focus on SUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 27 publications
7
101
0
2
Order By: Relevance
“…A second kind is combined treatments, EVIDENCE BASE UPDATE ASU in which ASU behavioral treatment is coordinated with medication intervention for a co-occurring disorder. For example, Riggs and colleagues have investigated CBT-I for ASU combined with stimulant medication for attention disorders (Riggs et al, 2011) and antidepressants for mood disorders (Riggs et al, 2007). 2.…”
Section: Discussionmentioning
confidence: 99%
“…A second kind is combined treatments, EVIDENCE BASE UPDATE ASU in which ASU behavioral treatment is coordinated with medication intervention for a co-occurring disorder. For example, Riggs and colleagues have investigated CBT-I for ASU combined with stimulant medication for attention disorders (Riggs et al, 2011) and antidepressants for mood disorders (Riggs et al, 2007). 2.…”
Section: Discussionmentioning
confidence: 99%
“…The manual that was used was chosen because of its feasibility and empirical support as a psychosocial treatment for SUD in adolescents with co-occurring psychiatric and substance use disorders. 13 Other studies also demonstrate the efficacy of MI/CBT as a treatment for adolescent SUD. 1,14 The MI/CBT consisted of hour-long, weekly individual sessions and could include up to three family sessions.…”
Section: Methodsmentioning
confidence: 97%
“…[18] One subsequent RCT (126 people aged 13-19 years with depression, comorbid substance abuse disorder and conduct disorder) found no significant difference between fluoxetine plus CBT and CBT plus placebo in remission rates for depression (CDRS score 28 or less) after 16 weeks of treatment (70% with combined treatment v 52% with CBT alone, P = 0.07). [36] It found that combined treatment significantly improved depressive symptoms (measured by CDRS) compared with CBT alone (effect size 0.78; P = 0.04).…”
Section: Fluoxetine Plus Cbt Versus Fluoxetine Alonementioning
confidence: 95%